The Effectiveness of Customer Reviews in the Tourism Industry - Khan, Ghazan Mohammad Shah (2019)
This study was planned with the purpose of understanding the effectiveness of online consumer reviews on purchase intentions and consumer behavior. Research began by reviewing previous literature relevant to the topic, published over the past 10-15 years. Four major hypotheses were developed after identifying literature gaps and potential topics for study. These were put to test after the study’s methodology was formulated. A questionnaire was developed for this purpose and shared online. There were 159 respondents, half being male and the other half being female. The first hypothesis developed questioned whether consumers consider third-party review sites more credible than other platforms for reviews. Results showed positive responses that supported this theory. The second hypothesis questioned the recurring trend of brand immunity to customer reviews (both positive and negative), specifically, if and how well-known brands are immune to online customer reviews. Results from the study indicated that consumers do not consider negative reviews when it comes to a well-known brand while positive reviews slightly enhanced sales. This may be a point of interest for lesser known brands to research upon so that they can progress by building similar levels of credibility and quality certainty. In addition to this, the third hypothesis sheds light on moderate reviews and their effect on increasing purchase intentions. The results received supported this hypothesis, emphasizing the importance of moderately valenced reviews. Finally, the questionnaire tested the effect of extremely positive reviews on consumers’ purchasing intentions. Research clearly showed that extremely positive reviews resulted in a negative consumer attitude which may decrease their purchase intentions. Extremely positive reviews are perceived as fake or biased by potential consumers. This dissertation contributes its own set of results through its own sample of participants by using a questionnaire method. Previous studies limited their tests to one website or one platform before deriving conclusions. Overall, three out of four hypotheses formed by this study were proven correct. However, the second hypothesis, brand immunity to positive and negative online reviews was proven to be incorrect, as positive reviews indicated a positive relationship with purchase intentions.